Between Europeanisation and Local Legacies: Holocaust Memory and Contemporary Anti-Semitism in Romania. Issue 2 (May 2021) - Cârstocea, Raul
This article addresses the persistence of anti-Semitism in Romania, placed in the context of some recent debates concerning the memory of the Holocaust in the country, as well as in the area of Central and Eastern Europe more broadly. It argues that, despite significant improvements in terms of legislation, the memory of the Holocaust remains a highly contested issue in contemporary Romania, torn between the attempts to join in the European memory of the Holocaust and local legacies that on the one hand focus primarily on the suffering of Romanians under the communist regime, and on the other perform a symbolic "denationalisation" of the Jewish minority in the country, whose own suffering is thus excised from national memory. It does so by focusing in particular on the debates surrounding the adoption of Law 217/2015, meant to clarify earlier legislation on Holocaust denial, and comparing them with those prompted by the Ukrainian "memory laws" passed in the same year. Taking into account both the national and international reactions to these very different pieces of legislation, the article shows the still-persisting discrepancy between a (mostly Western) "European" memory of the legacy of the twentieth century and local memory topoi characteristic of the countries that were part of the former socialist bloc.